Biomaterials-based phototherapy for bacterial infections - Wu, Guangzhi; Xu, Zhuo; Yu, Yue; Zhang, Minglei; Wang, Shuaishuai; Duan, Shuo; Liu, Xilin (Frontiers in Pharmacology, 2024)
Bacterial infections and antibiotic resistance are global health problems, and current treatments for bacterial infections still rely on the use of antibiotics. Phototherapy based on the use of a photosensitizer has high efficiency, a broad spectrum, strong selectivity, does not easily induce drug resistance, and is expected to become an effective strategy for the treatment of bacterial infections, particularly drug-resistant infections. This article reviews antimicrobial strategies of phototherapy based on photosensitizers, including photodynamic therapy (PDT), photothermal therapy (PTT), and their combination. These methods have significant application potential in combating multi-drugresistant bacterial and biofilm infections, providing an alternative to traditional antibiotics and chemical antibacterial agents.